The Impact of Dalteparin (Fragmin®) on Thrombin Generation in Pregnant Women with Venous Thromboembolism: Significance of the Factor V Leiden Mutation - Christian, Schambeck M.; Eberl, Edda; Geisen, Ulrich; Grossmann, Ralf; Keller, Franz (Thrombosis and Haemostasis, 2001)
Hypercoagulability is observed in patients with inherited thrombophilia, e.g. factor V Leiden (FVL) mutation. Pregnancy represents a hypercoagulable state as well. This study addresses the effects of the FVL mutation on haemostatic activation during pregnancy as indicated by prothrombin fragments (F1+2). 233 pregnant women with no history of venous thromboembolism were studied. Additionally, two patient groups (25 pregnant FVL carriers and 36 pregnant women without thrombophilic diathesis) in whom low molecular weight heparin (dalteparin) was used prophylactically against rethrombosis were investigated.None of the women developed clinical signs of venous thromboembolism during pregnancy or after delivery. Untreated women exhibited substantial hypercoagulability. F1+2 levels were similar in FVL carriers and non-carriers (difference n. s.). After sufficient adjustment for anti-factor Xa activity (≥0.15; ≤0.4 U/mL), heparinized women without any thrombophilic diathesis had significantly lower levels of F1+2 than untreated pregnant women. This was evident only in the first and second trimenon (p <0.01). F1+2 levels in heparinized FVL carriers were quite similar to the levels observed in untreated pregnant women, however. In conclusion, our data support the thesis that in comparison to asymptomatic patients, thrombin generation is exaggerated in symptomatic FVL carriers. Coagulation activation during pregnancy can be reduced by dalteparin.
Keywords: Pregnancy; thromboembolism; thrombophilia; low molecular weight heparin